2011
DOI: 10.4103/0974-8520.85741
|View full text |Cite
|
Sign up to set email alerts
|

Standard manufacturing process of Makaradhwaja prepared by Swarna Patra-Varkha and Bhasma

Abstract: Makaradhwaja is an important Kupipakwa Rasayana. It is prepared by using Swarna (gold), Parada (mercury) and Gandhaka (sulfur) in different ratios, i.e. 1:8:16, 1:8:24 and 1:2:4, respectively. The amount of Gandhaka in the Jarana process is directly proportional to the increase in therapeutic efficacy and reduces the toxicity of the product. Specific temperature pattern for the preparation of Makaradhwaja has been followed. In the present study Swarna, Parada and Gandhaka were taken in the ratio 1:8:24, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…By far the research works concerned on Makaradhwaja ; this is the highest percentage of gold reported till date. This further supports the conclusion of prior resercher[21] as Swarna Varkha was used in the preparation. Duration of trituration of Swarna Pishti , duration of Paka ( Madhyamagni and Tivragni , at the time of sublimation) and to a certain extent, errors in sample preparation may be the reasons for low quantity of gold reported in TM.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…By far the research works concerned on Makaradhwaja ; this is the highest percentage of gold reported till date. This further supports the conclusion of prior resercher[21] as Swarna Varkha was used in the preparation. Duration of trituration of Swarna Pishti , duration of Paka ( Madhyamagni and Tivragni , at the time of sublimation) and to a certain extent, errors in sample preparation may be the reasons for low quantity of gold reported in TM.…”
Section: Discussionsupporting
confidence: 86%
“…Quantity of gold present in TM (7.2976 ppm) was far below the levels reported[21] (268 ppm), although it is nearly equal to the levels reported initially (7.65 ppm). It is to be noted that in first case[21] TM had been prepared from Hingulottha Parada , whereas in other works[8] done it was prepared from by Ashtasamskarita Parada and Dwiguna Balijarana from Patra of Swarna . In the present work, Makaradhwaja was prepared by Ashtasamskarita Parada and subsequently Triguna and Shadguna Balijarana were carried out with Swarna Varkha .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…[ 15 ] However, Makaradwaja samples received from Gujarat Ayurved University, analyzed in our lab, have been found to contain gold at 20–270 ppm [ Table 1 ]. It has been explained that the variation of gold content depends on the type of gold used[ 16 ] or the extent sulfur used. [ 17 ] Some preparations even report Poorna Chandrodayam (a preparation similar to that of Makaradwaja ) having close to 9% gold!…”
Section: Analysis Of Mercurials Prepared With Sulfurmentioning
confidence: 99%
“…Specific action on cell-mediated immunity is proved by its immune-modulator action [ 5 ]. In experimental and clinical studies, it is found effective in diabetes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%